ELECTORAL VIOLENCE IN KADUNA STATE: THE IMPLICATION FOR PEACE AND DEVELOPMENT - Abdullahi Umar; Abubakar Abdullahi Muhammad; Awwal Muhammad Shafiu; Abdulrahim Mahmud Dogara; Amina Lawal (International Studies Journal)
The goal of the paper is to examine electoral violence in Nigeria and how it has affected Kaduna State peace and development. By conducting a thorough interview, the study uses a qualitative methodology. The study used the political legitimacy and effectiveness theories. The concept of political legitimacy is inextricably intertwined with the issues of political change, regardless of whether governments, political systems, or institutions comply with the traditional standards of legitimacy as subscribed in a democratic process of free and fair elections. The study found that electoral violence has turned into a predictable occurrence in Nigeria's political system and should therefore not be escalated to destructive levels against people's lives and property, regardless of their ethnic or religious differences.The paper also found that there are a number of variables, such as poverty, unemployment, and inadequate voter education that contribute to election violence in Kaduna State. Loss of life and property, uncertainty, and illegitimacy are only a few of the effects of these circumstances. The paper suggests that the government should focus on the prevention in order to solve election violence in Kaduna State by reducing the number of firearms in the hands of unlicensed people and giving job chances to young people who are unemployed. Despite their disparities in ethnicity and religion, the paper's conclusion argues that Kaduna State's many subpopulations must work together.